A New Way for Access and Maintenance of Offshore Wind Farms: The Use of Cableway to Reduce Cost and Improve Accessibility. Issue 3 (June 2013) - Gracchi, Massimo; Meroni, Luigi; Betteto, Piergiorgio
This work proposes a new method in order to deploy an affordable and reliable way for maintenance when it is necessary to access to offshore wind farms. The new system, based on cableway infrastructure is aimed to allow a lower cost of maintenance compared to other system for the same kind of operation but also to improve the reactivity and accessibility compared to them. Maintenance activities are taken into consideration in term of cost, period, nature, accessibility of wind farm, kind of maintenance we want/need to use in order to ameliorate the availability/reliability of the wind farm. Five different configurations with related cableway system are analyzed in order to demonstrate that facing a reasonable increasing of Capital Cost, sizable saving and extra revenue can be obtained if projected on the expected life of wind farms